2006
DOI: 10.1212/01.wnl.0000208957.88534.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of noninvasive ventilation on ALS patients and their caregivers

Abstract: Respiratory muscle weakness has a greater impact on quality of life (QoL) than overall ALS severity. Noninvasive ventilation (NIV) improves QoL despite ALS progression. NIV has no impact on most aspects of caregiver QoL and does not significantly increase caregiver burden or stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 39 publications
2
73
0
3
Order By: Relevance
“…Current interventions are limited to slowing disease progression or palliating symptoms such as dysphagia, weight loss, and respiratory muscle weakness [3,4] and the recommended interventions, such as gastrostomy and noninvasive ventilation (NIV), tend to be required by people with ALS (pwALS) in later stages of the disease [3,5]. Gastrostomy has been shown to improve nutrition, and NIV can help relieve the symptoms experienced due to diaphragmatic weakness, interventions which have improved prognosis and quality of life [6][7][8][9] without increasing caregiver burden [7]. Rates of uptake for NIV in the UK may currently be low [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current interventions are limited to slowing disease progression or palliating symptoms such as dysphagia, weight loss, and respiratory muscle weakness [3,4] and the recommended interventions, such as gastrostomy and noninvasive ventilation (NIV), tend to be required by people with ALS (pwALS) in later stages of the disease [3,5]. Gastrostomy has been shown to improve nutrition, and NIV can help relieve the symptoms experienced due to diaphragmatic weakness, interventions which have improved prognosis and quality of life [6][7][8][9] without increasing caregiver burden [7]. Rates of uptake for NIV in the UK may currently be low [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, acceptance of gastrostomy is related to a lack of pleasure obtained from oral intake and the inability to eat independently [26]. In a broader context, prospective research has demonstrated significant burden and psychological distress in caregivers of pwALS [7,27,28], but the relationship with palliative interventions has not always been explored [27].…”
Section: Introductionmentioning
confidence: 99%
“…The models of telehealth described in this review are intensive and require a large number of specialist staff at considerable cost, but monitoring could become more automated, reducing staff burden and making systems more affordable. (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…14,15,[27][28][29] NIV improved sleep quality shortly after initiation 27,29 and up to 10 months 27 or longer, 15,29 whereas daytime sleepiness decreased. 15,28 Subjects with bulbar involvement seemed to be less tolerant of NIV, but subjects who tolerated NIV, even those with severe bulbar involvement, seemed to achieve better sleep quality.…”
Section: Niv and Sleepmentioning
confidence: 98%